Mini‐synplastomes for plastid genetic engineering. Issue 2 (24th October 2021) - Occhialini, Alessandro; Pfotenhauer, Alexander C.; Li, Li; Harbison, Stacee A.; Lail, Andrew J.; Burris, Jason N.; Piasecki, Cristiano; Piatek, Agnieszka A.; Daniell, Henry; Stewart, C. Neal; Lenaghan, Scott C.
Summary: In the age of synthetic biology, plastid engineering requires a nimble platform to introduce novel synthetic circuits in plants. While effective for integrating relatively small constructs into the plastome, plastid engineering via homologous recombination of transgenes is over 30 years old. Here we show the design–build–test of a novel synthetic genome structure that does not disturb the native plastome: the 'mini‐synplastome'. The mini‐synplastome was inspired by dinoflagellate plastome organization, which is comprised of numerous minicircles residing in the plastid instead of a single organellar genome molecule. The first mini‐synplastome in plants was developed in vitro to meet the following criteria: (i) episomal replication in plastids; (ii) facile cloning; (iii) predictable transgene expression in plastids; (iv) non‐integration of vector sequences into the endogenous plastome; and (v) autonomous persistence in the plant over generations in the absence of exogenous selection pressure. Mini‐synplastomes are anticipated to revolutionize chloroplast biotechnology, enable facile marker‐free plastid engineering, and provide an unparalleled platform for one‐step metabolic engineering in plants.